SIKAP SISWA TERHADAP IKLIM SEKOLAH DI SMA NEGERI 3 PADANG PANJANG - safri, intan safrimanila; Rahmanelli, Rahmanelli (JURNAL BUANA, 2024)
Abstract The study discusses student attitudes toward school climate ate SMA Negeri 3 Padang Panjang. The purpose of this study is to describe and communicate with peers and theachers as well as the environment at with a quantitative. Data collection techniques in this study were using questionnaires, obsevations, and interviews. Informants involved in this study were student of class X and XI social studies who studied geography. The data analysis technique used was in accordance with the type of data collected in descriptive research. For analysis, the formula in the form of a percentage was used by Yusuf A Muri. The results of this study can be seen that there is now correlation between students attitude toward climate in learning geography at SMA Negeri 3 Padang Panjang in social studies class in the academic years 2021/2022.